Deepening Of Territorial Specialization in The Production of Agricultural Products (In the example of the suburbs of the city of Navoi) (Texas Journal of Agriculture and Biological Sciences, 2023)
In this article, the deepening of regional specialization in agricultural product cultivation and the factors affecting it are analyzed in the example of the outskirts of Navoi. The structure of crops, cropland and agricultural production indicators in Navoi suburban agriculture were studied in terms of economic categories, that is, farmers and peasant households, and farming organizations. Also, the volume of production of agricultural products per capita in the suburbs of Navoi City, the development of vegetable growing, potato growing, viticulture, and horticulture industries will be discussed